Brief psychological interventions for anxiety and depression in a secondary care adult mental health service: an evaluation. (8th October 2021) - Roberts, Kate; Travers-Hill, Emma; Coker, Siân; Troup, Jordan; Casey, Stephanie; Parkin, Katherine; Kim, Youngsuk
Abstract: Due to continuing pressures on the UK National Health Service's mental health services, there has been increased interest in the development of brief psychological interventions (BPIs). These interventions are usually defined as including selected components of established psychological interventions, delivered over fewer sessions, and by staff with less specialised training (paraprofessionals). Cognitive behavioural therapy (CBT)-based BPIs for anxiety and depression have been found to be helpful for clients with mild to moderate mental health problems. This project evaluates the introduction of BPIs for anxiety and depression in a secondary care adult mental health service, with clients experiencing moderate to severe mental health difficulties. The service developed CBT-based manuals for anxiety (anxiety management) and depression (behavioural activation) BPIs. The BPIs were delivered by mental health workers without core therapeutic training, who were offered training and group supervision by psychologists in the team. Measures of anxiety (GAD-7), depression (PHQ-9), wellbeing (SWEMWBS) and functioning (WSAS) were completed at the start and end of treatment. The data reported from a 2-year period suggest that BPIs are associated with reductions in symptoms of anxiety and low mood, and improvements in wellbeing and functioning. Whilst this is a small-scale initial evaluation, the results are promising for the potential benefit of BPIs for clients in secondary care settings. Given that this new way of working has possible additional benefits such as improving access to psychological treatment and cost-effectiveness, further research in the area is warranted and encouraged. Key learning aims: (1) To overview the current evidence for BPIs. (2) To outline a possible model for offering BPIs in secondary care. (3) To illustrate the potential positive effects of BPIs within a secondary care population. (4) To consider the need for future research and development of BPIs.